The role of mother-adolescent relationship quality in moderating the effect of adolescent anxiety on psychosocial functioning - Clarissa Lui; Kylie Burke; Cassandra K. Dittman (Australian Journal of Psychology)
Objective The effects of anxiety on adolescents’ psychosocial outcomes are well established, but little consideration has been given to the potential influence of the parent-adolescent relationship in moderating these effects. This study examined the moderating role of parent-adolescent connectedness and hostility in the association between anxiety and adolescent psychosocial functioning (measured by positive development [PD] and oppositional defiant behaviour [ODB]) within a community sample of mothers of adolescents.Method Participants were 723 Australian mothers (M age = 44.05 years, SD = 5.97) of adolescents aged 11 to 17 years (M = 14.32 years, SD = 5.97; 49% male). Participants completed an online survey comprising measures of parent-adolescent relationships, parenting practices, parental psychological distress, and adolescent anxiety and psychosocial functioning.Results Consistent with the first hypothesis, results from hierarchical regression analyses revealed that adolescent anxiety, connectedness, and hostility were independent predictors of PD and ODB. Inconsistent with predictions, parent-reported anxiety had a stronger, negative association with PD when mothers viewed the relationship with their adolescents as more connected and less hostile. Neither parent-adolescent connectedness nor hostility moderated the association between maternal reported adolescent anxiety and ODB.Conclusions Further longitudinal research is needed to understand how the parent-adolescent relationship context might affect outcomes and inform family-based prevention and intervention efforts for at-risk youth with anxiety symptomatology.